Studying the factors that increase the shelf-life in citrus fruits / \c Muhamad Hakim Mat Nasir - Muhamad Hakim Mat Nasir (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
Navel oranges are prone to develop postharvest spoilage during storage. There are numerous factors contributing to spoilage such as temperature , humidity and fungal attack. The present research aims is to investigate the environmental factors (e.g. temperature & relative humidity ) affecting the shelf -life of citrus fruit and to determine the effect of biopolymer coating on the shelf - life of citrus fruit. In this research, chitosan , alginate and guazatine had been employed as fruits coating. The influence of altering storage temperature and relative humidity on the incidence of postharvest spoilage in term of weight loss, size, shape, color and pH on the physiological behavior of oranges was examined.